Adult Cystic Nephroma: A Rare Incidental Tumor of the Kidney - Rijhsinghani, Archana N (Annals of Pathology and Laboratory Medicine, 2025)
Mixed epithelial and stromal tumors/adult cystic nephroma are rare, biphasic, incidentally detected tumors of the kidney. They require surgical intervention. Rare cases show malignant morphology.